Імплементація цифрових технологій у процеси антикризового управління сільськогосподарських підприємств - Халатур, Світлана Миколаївна; Khalatur, Svitlana; Клименко, Станіслав; Klymenko, Stanislav (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2025)
У статті досліджено роль цифрових технологій в антикризовому управлінні сільськогосподарськими підприємствами в умовах сучасних викликів, таких як воєнні дії, економічна нестабільність і кліматичні зміни. Обґрунтовано, що цифровізація стає ключовим чинником підвищення стійкості, ефективності та адаптивності аграрного сектору. Розглянуто потенціал впровадження таких інструментів, як ERP-системи, хмарні сервіси, IoT, технології штучного інтелекту, блокчейну та аналізу великих даних. Проаналізовано сучасні наукові підходи до цифрової трансформації управлінських процесів, визначено етапи імплементації цифрових рішень та окреслено технічні, організаційні й фінансові аспекти їх застосування. Визначено основні переваги та виклики імплементації цифрових технологій в антикризове управління сільськогосподарських підприємств. Зроблено висновок, що інтеграція цифрових технологій у систему антикризового управління сприяє стратегічній стійкості та конкурентоспроможності аграрних підприємств у довгостроковій перспективі. The article examines the current aspects of the introduction of digital technologies into the anti -crisis management system of agricultural enterprises. It is determined that the agrarian sector of Ukraine operates under constant pressure of external threats, in particular hostilities, economic instability, climatic changes, fluctuations in world markets and logistics problems, which requires the introduction of new, innovative approaches to managing production and financial processes. The expediency of using digital tools such as ERP systems, Internet of things (IoT), Big Data, cloud services, drone technologies and elements of artificial intelligence to ensure flexible response to crisis situations, increase the efficiency of management decisions, and adaptability of enterprises to enterprises, adaptability of enterprises, adaptability of enterprises, adaptability of enterprises, adaptability of enterprises, adaptability of enterprises, adaptability of enterprises, adaptability of enterprises, adaptability of enterprises, adaptability of enterprises, and enhancement of enterprises, and increasing the efficiency of enterprises and pre-agent. A critical review of modern scientific approaches to the digitalization of the agricultural sector has been carried out and the experience of implementing digital decisions in agribusiness was analyzed. The role of digital technologies in real time for monitoring, yield forecasting, risks management, reasonable management decision-making, accounting automation, cost reduction, increased energy efficiency, improvement of logistics and ensuring transparency of business processes are revealed. The main stages of digital transformation of anti -crisis management are described, starting with the diagnosis of internal and externalthreats, assessing resource potential, choosing relevant digital tools, for staff training, forming digital culture andevaluating the effectiveness of innovations. Organizational, technical and financial aspects of digital decisionimplementation, including the need for updating IT infrastructure, integration of new platforms with current systems,development of security policies, formation of a legal framework, attracting investments and data protection, have beenidentified. The article provides recommendations for increasing the stability of agricultural enterprises with digitaltechnologies, which will contribute to their sustainable development, competitiveness and effective functioning in theface of constant changes
Implementation of digital technologies in the processes of anti-crisis management of agricultural enterprises
Keywords: цифрові технології; digital technologies; антикризове управління; anti-crisis management; аграрні підприємства; аграрні підприємства; ефективність управління; management efficiency; стійкість; sustainability